PENGEMBANGAN MEDIA PEMBELAJARAN DIORAMA SIKLUS AIR PADA MATA PELAJARAN IPA KELAS V UPAYA MENINGKATKAN HASIL BELAJAR SISWA DI SDN DRANGONG 2 - Syifa Maulida; Syifa Wardatul Jannah; Dinda Syafariza; Laila Munawaroh (Jurnal Pendidikan Dasar, 2025)
Students experience learning problems due to monotonous media usage in science lessons in fifth grade elementary school. This study created a water cycle diorama as a learning medium. Monotonous media usage causes students to lack motivation and fail to understand concepts properly. This study used the Research and Development (R&D) method using the ADDIE model. After being validated by subject matter experts and media experts, the developed media was tested on students. The validation results showed a very high level of feasibility, with subject matter expert scores of 78.5% and 93.8% and media expert scores of 72.9% and 80%. The diorama was able to visualize the water cycle process in an interesting and easy-to-understand manner, as indicated by the 88% response from students. The water cycle diorama is considered feasible, practical, and effective as a solution to overcome monotonous learning media and improve students' conceptual understanding and learning outcomes in Grade 5 science. Students' learning outcomes also increased significantly after using the media, as indicated by the increase in scores before and after learning.